The course and outcomes of COVID-19 in patients with ANCA-associated systemic vasculitis, receiving biological therapy (Rituximab, Mepolizumab): The results of the first 8 months of the pandemic - T. V. Beketova; V. V. Babak; M. D. Suprun (Научно-практическая ревматология)
Objective. Currently, the issues of the effect of anti-B cell therapy or inhibitor of interleukin 5 on the risk of COVID-19 infecting and outcomes in patients with ANCA-associated vasculitis (AAV) has not been completely studied. We present an analysis of the COVID-19 course and outcomes in AAV patients treated with rituximab or mepolizumab from one rheumatology center registry.Methods. From November 11 to November 15, 2020, a cross-sectional study was conducted using telephone and online surveys, and information was collected from all 128 AAV patients treated with rituximab in V.A. Nasonova Research Institute of Rheumatology. Patients mean age was 51 (20–81) years, 61.7% were women. Granulomatosis with polyangiitis (GPA) was diagnosed in 58 patients, microscopic polyangiitis (MPA) – in 38, eosinophilic granulomatosis with polyangiitis (EGPA) – in 24 (including 54.2% of ANCA-negative cases), and AAV with uncertain nosological affiliation – in 8 patients. Due to the disease activity or a high risk of AAV recurrence during the pandemic rituximab was prescribed in 60/126 (47.6%) patients, and mepolizumab – in 6 cases.Results. In the spring of the pandemic (until May 2020), the incidence of COVID-19 in AAV patients treated with rituximab was 4.3%, the disease course was relatively favorable. All patients recovered. At month 3–6, antibodies to SARS-CoV-2 IgG persisted in only 1 out of 4 patients. Since September 2020, the incidence has increased 3-fold, with a more severe course of COVID-19. In total, in the period until November 11, 2020, COVID-19 was diagnosed in 17.2% (22/128); the mean age of patients was 55 (25–81) years; 54.5% were women. 21/22 patients were on rituximab therapy, 2 patients had mepolizumab therapy (including 1 case after previous rituximab therapy). COVID-19 incidence was lower in patients with GPA (15.5%) vs MPA and EGPA (21.1% and 20.8% respectively). The mortality rate was 13.6%, including 2 patients with MPA and 1 patient with GPA. When analyzing the 5-year survival rate according to the registry of AAV patients treated with rituximab, prognosis worsening was noted; in 2020 there were 3 deaths due to COVID-19, in the previous 5 years – only 2 deaths.Discussion. Taking into account the fact the mechanisms of AAV and severe COVID-19 are largely synergistic (primarily in the context of microvascular COVID-19 lung vessels obstructive thromboinflammatory syndrome as manifestation of the acute inflammatory syndrome), the activity of AAV can potentially contribute to the disease onset and a severe course of COVID-19. Given the previously published information on the use of rituximab during the COVID-19 pandemic for various diseases, it seems that B cell depletion, without reducing the risk of infection, may have a protective effect with regard to the risk of severe/catastrophic COVID-19, which, however, can be insufficient in AAV patients. Further analysis of COVID-19 cases in patients with AAV and other immuno-inflammatory rheumatic diseases is exceptionally important.